A KCNC3 mutation causes a neurodevelopmental, non-progressive SCA13 subtype associated with dominant negative effects and aberrant EGFR trafficking. - Swati Khare; Jerelyn A Nick; Yalan Zhang; Kira Galeano; Brittany Butler; Habibeh Khoshbouei; Sruti Rayaprolu; Tyisha Hathorn; Laura P W Ranum; Lisa Smithson; Todd E Golde; Martin Paucar; et al. (PLoS ONE, 2017)
The autosomal dominant spinocerebellar ataxias (SCAs) are a diverse group of neurological disorders anchored by the phenotypes of motor incoordination and cerebellar atrophy. Disease heterogeneity is appreciated through varying comorbidities: dysarthria, dysphagia, oculomotor and/or retinal abnormalities, motor neuron pathology, epilepsy, cognitive impairment, autonomic dysfunction, and psychiatric manifestations. Our study focuses on SCA13, which is caused by several allelic variants in the voltage-gated potassium channel KCNC3 (Kv3.3). We detail the clinical phenotype of four SCA13 kindreds that confirm causation of the KCNC3R423H allele. The heralding features demonstrate congenital onset with non-progressive, neurodevelopmental cerebellar hypoplasia and lifetime improvement in motor and cognitive function that implicate compensatory neural mechanisms. Targeted expression of human KCNC3R423H in Drosophila triggers aberrant wing veins, maldeveloped eyes, and fused ommatidia consistent with the neurodevelopmental presentation of patients. Furthermore, human KCNC3R423H expression in mammalian cells results in altered glycosylation and aberrant retention of the channel in anterograde and/or endosomal vesicles. Confirmation of the absence of plasma membrane targeting was based on the loss of current conductance in cells expressing the mutant channel. Mechanistically, genetic studies in Drosophila, along with cellular and biophysical studies in mammalian systems, demonstrate the dominant negative effect exerted by the mutant on the wild-type (WT) protein, which explains dominant inheritance. We demonstrate that ocular co-expression of KCNC3R423H with Drosophila epidermal growth factor receptor (dEgfr) results in striking rescue of the eye phenotype, whereas KCNC3R423H expression in mammalian cells results in aberrant intracellular retention of human epidermal growth factor receptor (EGFR). Together, these results indicate that the neurodevelopmental consequences of KCNC3R423H may be mediated through indirect effects on EGFR signaling in the developing cerebellum. Our results therefore confirm the KCNC3R423H allele as causative for SCA13, through a dominant negative effect on KCNC3WT and links with EGFR that account for dominant inheritance, congenital onset, and disease pathology.